Variability and variation in Rhyncholestes raphanurus Osgood (Paucituberculata, Caenolestidae) - González Chávez, Baltazar (2020)
Background: Caenolestids are a group of poorly known South American marsupials with a restricted distribution in Páramo and Subpáramo environments of the Andes from Colombia and western Venezuela to Bolivia (represented by the genera Caenolestes and Lestoros), and Valdivian rainforest in southern Chile (including a separate population in Chiloé Island) and Argentina, where a single species lives: the Long-nosed shrew opossum (Rhyncholestes raphanurus). The objectives of this work were to analyze the intraspecific variability of R. raphanurus, which includes an anatomical description of the skull and dentition, describe its geographic variation, test for sexual dimorphism, and assess potential differences between continental and Island populations. Methods: Linear Mossimann-transformed variables were used to assess sexual differences within a large population (La Picada), compare sexes within other continental populations, and in a separate analysis, compare continental from Island samples. A full model Principal Components Analysis was performed to assess differences between males and females of the continental and Island populations. A thorough description of the skull and teeth of the species and comparisons with other living Caenolestidae is presented. Results: Rhyncholestes raphanurus presents little geographic variation, even between Island and continental populations. Similarly, we found no significant difference between sexes of this species in cranial and dental measurements. We provide a detailed description of cranial morphology and its variation, and also, the first description of the occipital bones, which haven’t been previously described for any Paucituberculata. Conclusions: Comparative studies of continental and Chiloé Island specimens support the treatment of R. raphanurus as a single valid species, especially since morphologic and morphometric differences fall within the extremes of continental populations. The morphology of R. raphanurus clearly separates this genus from other extant Caenolestidae, and in a much greater degree than the differences found between Lestoros and Caenolestes.